VISUAL ARTS AS A MEANS OF DEVELOPING CREATIVE SKILLS OF 3-4 GRADE STUDENTS - Цалковська, Катерина; Сіранчук, Наталія (SWorldJournal, 2023)
Art is one of the important components of the spiritual culture of human society. However, the transmission of information from one generation to another does not provide development of society. The most important condition for such development is the abi